MATHEMATICAL MODELLING OF TEMPERATURE DISTRIBUTION IN VERTICAL OIL PIPE IN DEEP WATER - HARAHAP (NIM : 10108047); Pembimbing 1 : Dr. Agus Yodi Gunawan; Pembimbing 2 : Muh, SOPHIATUDIEN
In this final project we study mathematic model of temperature distribution in a vertical pipe in deep water. The model is devide from the mass, momentum, and energy conservations. The goal of this project is to find the point in pipe where the changing of fluid phase will take place. This changing is due to the difference of temperature inside and outside pipe. The results show the changing of fluid phase are affected by material pipe.